Understanding the root of the problem for tackling pea root rot disease - Trenk, Nicolas Karl; Pacheco-Moreno, Alba; Arora, Sanu (Frontiers in Microbiology, 2024)
Pea (Pisum sativum), a crop historically significant in the field of genetics, is regaining momentum in sustainable agriculture due to its high protein content and environmental benefits. However, its cultivation faces significant challenges from root rot, a complex disease caused by multiple soil-borne pathogens prevalent across most pea growing regions. This disease leads to substantial yield losses, further complicated by the dynamic interactions among pathogens, soil conditions, weather, and agricultural practices. Recent advancements in molecular diagnostics provide promising tools for the early and precise detection of these pathogens, which is critical for implementing effective disease management strategies. In this review, we explore how the availability of latest pea genomic resources and emerging technologies, such as CRISPR and cell-specific transcriptomics, will enable a deeper understanding of the molecular basis underlying host-pathogen interactions. We emphasize the need for a comprehensive approach that integrates genetic resistance, advanced diagnostics, cultural practices and the role of soil microbiome in root rot. By leveraging these strategies, it is possible to develop pea varieties that can withstand root rot, ensuring the crop's resilience and its continued importance in global agriculture.